Co-exposure to priority-controlled metals mixture and blood pressure in Chinese children from two panel studies. (1st August 2022) - Liu, Miao; Li, Meng; Guo, Wenting; Zhao, Lei; Yang, Huihua; Yu, Jie; Liu, Linlin; Fang, Qin; Lai, Xuefeng; Yang, Liangle; Zhu, Kejing; Dai, Wencan; et al.
Abstract: Metals may affect adversely cardiovascular system, but epidemiological evidence on the associations of priority-controlled metals including antimony (Sb), arsenic (As), cadmium, lead, and thallium with children's blood pressure (BP) was scarce and inconsistent. We conducted two panel studies with 3 surveys across 3 seasons among 144 and 142 children aged 4–12 years in Guangzhou and Weinan, respectively. During each seasonal survey, urine samples were collected for 4 consecutive days and BP was measured on the 4th day. We obtained 786 BP values and urinary metals measurements at least once within 4 days, while 773, 596, 612, and 754 urinary metals measurements were effective on the health examination day (Lag 0), and the 1 st, 2 nd, and 3 rd day preceding BP measurement (Lag 1, lag 2 and lag 3), respectively. We used linear mixed-effect models, generalized estimating equations and multiple informant models to assess the associations of individual metal at each lag day and accumulated lag day (4 days averaged, lag 0–3) with BP and hypertension, and Bayesian Kernel Machine Regression to evaluate the relations of metals mixture at lag 0–3 and BP outcomes. We found Sb was positively and consistently related to systolic BP (SBP), mean arterial pressure (MAP), and odds of having hypertension within 4 days, which were the strongest at lag 0 and declined over time. And such relationships at lag 0–3 showed in a dose-response manner. Meanwhile, Sb was the only contributor to the relations of mixture with SBP, MAP, and odds of having hypertension. Also, synergistic interaction between Sb and As was significant. In addition, modification effect of passive smoking status on the association of Sb and SBP was more evident in passive smokers. Accordingly, urinary Sb was consistently and dose-responsively associated with increased BP and hypertension, of which Sb was the major contributor among children. Graphical abstract: Image 1 Highlights: Urinary antimony (Sb) was related to blood pressure (BP) and hypertension within 4 days. Relations of Sb and BP outcomes were strongest at lag 0 and dose-responsive at lag 0–3. Sb was the major contributor to relations of metals mixture with BP outcomes. Passive smoking status modified the association of Sb and systolic BP.